Using easily prepared carbon nanodots to improve hole transport capacity of perovskite solar cells. (June 2019) - Li, Zhiqi; Liu, Chunyu; Zhang, Xinyuan; Guo, Jiaxin; Cui, Houxiao; Shen, Liang; Bi, Yanfeng; Guo, Wenbin
Abstract: Poly(3, 4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) is the most widely-used transparent anode material of commercialization. However, the partially bonding between PSS and PEDOT greatly decreases the structural and electronic homogeneity of PEDOT:PSS system. In view of their molecular structure and functional groups, a S, N co-doped carbon nanodots (CNDs) was developed as ameliorant to prepare PEDOT:PSS:CNDs hole transport layer. The uncombined S double bond introduces more microcosmic interstice inside CNDs, accompanying with many N-rich amino on the surface. This highly reactive products can band the redundant PSS and remove the insulating component from PEDOT:PSS mixture, leading to the conductivity and structural homogeneity improvement. The hole-transport capability of PEDOT:PSS:CNDs is systematically investigated in inverted planar hetero-junction (PHJ) perovskite solar cells (PSCs) fabricated in air, and an optimized power conversion efficiency (PCE) of 18.03% was achieved, which is superior to PEDOT:PSS based PSCs produced under atmospheric. This work offers a new strategy to improve the charge transfer capability of PEDOT:PSS in PSCs. Graphical abstract: Image 1 Highlights: The CNDs were rationally designed according to the structural characteristic and reactive functional groups of PEDOT:PSS. The synthesis of CNDs were simplistic, low-cost, environment-friendly, and suitable for mass production. The CNDs own lots of functional amidogen exposure on the surface accompanying with multitudinous hollow pores inside. The CNDs shows competitive ability for separating PEDOT with PSS from PEDOT:PSS system. The optimized PEDOT:PSS:CNDs own enhanced conductivity and hole extraction capability for optoelectronic applications.